Interrogation and torture : integrating efficacy with law and morality - Barela, Steven J., 1971-; Fallon, Mark; Gaggioli, Gloria; Ohlin, Jens David (New York, NY : Oxford University Press, 2020)
This text develops a comprehensive discussion regarding the legality of torture and the efficacy of interrogation. Scientific research has concluded that torture is not effective. So, what interrogational methods are effective and how does one deploy those methods in such a way that is consistent with law and morality?
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 13, 2020).
Keywords: Torture -- Moral and ethical aspects; Torture (International law); Military interrogation; Police questioning; Torture -- Law and legislation -- United States; Society; Ethics & moral philosophy